ANGLIZATION OF SCIENTIFIC AND EDUCATIONAL NETWORK DISCOURSE: LEXICO-THEMATIC SCOPE AND SOCIAL FACTORS OF THE PHENOMENON - Kononenko, Olha (Linguistic Bulletin (Movoznavchyi Visnyk), 2024)
Introduction. Borrowing process happens constantly, reflecting new realities of our life, giving them new names. But no it is possible to allow such processes to take place spontaneously, unmotivated, because it is often attractive a borrowed lexeme is completely unproductive in the system of the modern Ukrainian language. The purpose of the research is to analyze the provisions of the legislative framework regarding the maintenance of the functions of the English language in Ukraine, to investigate the lexical-semantic basis of network discourse, the functioning of barbarisms and the expediency of their use in the relevant contexts. Results. Anglicization manifests itself not only in youth slang, in the field of mass culture, alleys in industry terminologies and, which is the latest in the history of the Ukrainian literary language, in official business communication. The Government of Ukraine promotes the globalization and Europeanization of the scientific and educational environment, motivating it by integration into the world community. The Ukrainian language is being neutralized and the status of English is being transformed at the legislative level. Scientific and educational platforms as part of network discourse are affected by Anglicization even under the influence of mediatization of the spheres of science and education. After all, our mass media are full of foreign words, despite the fact that the Ukrainian language is capable of accurately conveying everything that needs its own name by its own means. Originality. The study of the language of online educational discourse on the subject of anglicisms provides grounds for asserting their unmotivated use. because at a turning point in history it is important to use all the possibilities of the native language. Conclusions. Despite the popularity and fashion for anlisms, the Ukrainian language has the resources and opportunities to nominate most of the syllogisms. The process of barbarization is unmotivated and dangerous for the Ukrainian language, but it is important to raise the rating and competitiveness of the Ukrainian language in the world.